2015
DOI: 10.1109/lawp.2014.2357058
|View full text |Cite
|
Sign up to set email alerts
|

A Broadband Patch Antenna Array With Planar Differential L-Shaped Feeding Structures

Abstract: This study involved developing a differential patch antenna array featuring a wide bandwidth and improved radiation patterns. The proposed patch array was fed by a planar, aperture-coupled, L-shaped feeding structure to achieve wideband operation. The differential feeding structure improved the current distribution of resonant modes, substantially improving the symmetry of radiation patterns. The array without differential excitation revealed an apparent deflected peak located at an observation angle of 10 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 8 publications
(7 reference statements)
0
23
0
Order By: Relevance
“…The proposed structure is a practical alternative to the costly, heavy, and bulky RWG feeder while maintaining the miniaturization, performance enhancement, cost reduction, and ease of integration with MPAs. In terms of bandwidth, the proposed array is able to attain a wide bandwidth in comparison to wideband radiation elements, such as U‐shaped parasitic patches, 16 L‐probe‐fed patch array, 17 and magneto‐electric‐dipole array 18 . According to Table 2, it can be concluded that the present design achieves wider fractional impedance bandwidth, higher radiation efficiency, higher aperture efficiency, and smaller size compared to the other MPA arrays.…”
Section: Fabrication and Measurement Resultsmentioning
confidence: 82%
“…The proposed structure is a practical alternative to the costly, heavy, and bulky RWG feeder while maintaining the miniaturization, performance enhancement, cost reduction, and ease of integration with MPAs. In terms of bandwidth, the proposed array is able to attain a wide bandwidth in comparison to wideband radiation elements, such as U‐shaped parasitic patches, 16 L‐probe‐fed patch array, 17 and magneto‐electric‐dipole array 18 . According to Table 2, it can be concluded that the present design achieves wider fractional impedance bandwidth, higher radiation efficiency, higher aperture efficiency, and smaller size compared to the other MPA arrays.…”
Section: Fabrication and Measurement Resultsmentioning
confidence: 82%
“…Accordingly, the dual Marchand balun is proposed in this design, which can be seen as two traditional Marchand baluns placed back‐to‐back, providing two pair of differential signals for the 2 × 2 antenna array. It has much simpler structure over the traditional design using the combination of hybrid coupler and two Wilkinson power dividers, as in References 25 and 28. As shown in Figure D, a half‐guided wavelength ( λ g /2) microstrip line in the middle is fed by port 1, which is used as the input port of the array.…”
Section: Design Of 2 × 2 Cp Dp Arraymentioning
confidence: 99%
“…The rectangular radiation patch is on the top surface of the Substrate 1, which is fed by an L‐shaped feeding structure. Here, a row of metalized via holes in is replaced by a cuboid metal, as shown in Figure (a). Through adjusting the dimension parameters of the L‐shaped feeding structure, a dual‐band performance can be achieved.…”
Section: Antenna Structurementioning
confidence: 99%
“…In this letter, to resolve the problem mentioned above, based on the structure mentioned in , a wideband and dual‐band antenna with directional patterns are proposed. Through exchanging the row of via holes in with a cuboid metal, the antenna can operate in a high‐order mode. In addition, the impedance matching at higher frequency can be improved.…”
Section: Introductionmentioning
confidence: 99%